Fat replacers in food system: A focus on ingredients, fabrication methods, and applications in food products - Ummul Fadillah; Andi Dirpan; Adiansyah Syarifuddin (Future Foods)
Fat is capable of imparting important sensory properties such as color, taste, texture, and odor to different foods, affecting overall consumer acceptance. There is a significantly high amount of fat in a diverse assortment of commodities, including meat, dairy, sauces, baked food, and oleogels. To reduce the high content and preserve consumer acceptability, fat replacers are often used such as proteins, complex carbohydrates, lipids, and their combinations, which have been widely investigated for use in various applications. Each type of replacers has unique characteristics that impact the quality of food product, with the processing methods playing a significant role. Emulsion and hydrocolloid methods, as well as the enzymatic synthesis of triacylglycerol, are recommended for dairy products, processed cheese, and low-fat meat products. Methods based on the enzymatic intersterification of the end product can also replicate the characteristics of natural fats (without trans) while crosslinking is recommended for pastry products. This shows the need to select the appropriate ingredients and methods for fat replacers which affect the physicochemical and sensory characteristics when applied to food products. Therefore, this review aimed to provide an in-depth assessment of fat replacers ingredients and methods used in products as a nutritional strategy with beneficial health consequences.